POS0910 A MULTIPLEX RT-QPCR KIT FOR EXPRESSION ANALYSIS OF INTERFERON-STIMULATED GENES AS A USEFUL TOOL FOR MOLECULAR STRATIFICATION IN LUPUS AND OTHER AUTOIMMUNE DISEASES - Qian, J.; Lu, L.; Cao, Z.; Fu, Q. (Annals of the rheumatic diseases, 2023)
It is recognized that the expression of interferon (IFN)-stimulated genes (IFN signature) plays a significant role in several autoimmune diseases (AIDs) [1], such as systemic erythematosus lupus (SLE), idiopathic inflammatory myopathies (IIM) and rheumatoid arthritis (RA). A quick and ready-to-use method to differentiate IFN activation state is clinically needed. This study aimed to conduct analytical validation of the Multiplex ISGs RT-qPCR Kit in clinical practice We designed a multiplex RT-qPCR method to provide IFN score covering both type I IFN and type II IFN by simultaneously detecting the expression of 3 IFN stimulated genes (ISGs), IFI44, MX1(type I ISGs), and IRF1(type II ISG), relative to one housekeeping gene (HPRT1). Measurements were performed on mRNA extracted from the peripheral blood cells of patients with multiple AIDs. The relative expression of each target gene (T/R) was calculated via 2^-ΔCT. The T/R of each target gene was then normalized as the following: T/R subject - Mean HC/ SD HC. IFN score was calculated as the mean of the normalized T/R of three target genes. Scores higher than the mean of HC plus two SD were designated IFN score high; otherwise, IFN score low. Analytical validation was performed to assess compliance rate, accuracy and method detection limit. Significantly elevated IFN scores were found in SLE(n=116), IIM(n=118), and RA(n=17) compared to other AIDs and HC. Four distinct subpopulations of SLE patients were observed: Thirty-five percent of SLE patients exhibited elevation of all three genes, indicating both type I and type II IFN pathways were activated. 44% of SLE patients had elevated expression of type I ISGs but no change in the type II ISG suggesting only type I IFN pathway was activated. 15% SLE patients presented no elevated expression of ISG gene. And 6% SLE patients only showed increased expression of IRF1 without overexpression of other 2 Type I ISGs, suggesting they probably only had type II IFN pathway activated. We repeated the tests. The compliance rate was 100% and accuracy was 100% with a CV of 0.36%. The method detection limit was 0.61 ng/μL. Using the Multiplex® ISGs RT-qPCR Kit, we assessed the IFN score in multiple AIDs. The analytical validation of the kit reveals that it is a reliable, reproducible diagnostic tool that will be useful in clinical practice but may require confirmation in larger-scale trials. [1]L. Rönnblom, and M.L. Eloranta, The interferon signature in autoimmune diseases. Curr Opin Rheumatol 25 (2013) 248-53. The authors thank the patients for participating in the study. None Declared. [Display omitted]